DIFFERENCES IN CERTAIN KINANTROPOLOGICAL CHARACTERISTICS OF ELEMENTARY SCHOOL STUDENTS AND THEIR COMPARISON WITH CROFIT NORMS - Marija Ćurić; Mijo Ćurić; Zvonimir Tomac (Sport Scientific And Practical Aspects, 2025)
The main purpose of this work is to identify differences in individual kinantropological characteristics of elementary school students and their comparison with Crofit norms. The research was conducted on a sample of 180 pupils from 5th to 8th grade of elementary school in Osijek. The sample was divided into sub-samples according to gender and age of students:5th grade students (21 boys and 23 girls), 6th grade students (25 boys and 29 girls), 7th grade students (19 boys and 21girls) and students of 8th grades (18 boys and 22 girls). The researched kinanthropological characteristics are two anthropometric measures (body height and body mass) from which is the result of body mass index, three motor abilities (coordination, MPN; flexibility, MPR; repetitive power, MPT) and functional ability (running 600, 800 meters; F600 for female pupils and F800 for male pupils). All tests are described in CRO FIT norms in the regular curriculum of physical and health education (Neljak and others, 2011).